2015
DOI: 10.14712/18059694.2015.95
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cervical Lymph Node Micrometastases in Patients with Squamous Cell Carcinoma of the Oral Cavity, Pharynx and Larynx

Abstract: Summary:Background: The goal of this prospective study was to determine the frequency of micrometastases in patients with squamous cell carcinoma (SCC) of the oral cavity, pharynx and larynx in whom elective neck dissection was indicated (cN0). Patients and Methods: A total of 12 patients (10 males and 2 females) were enrolled in the study. The age ranged 42-73 years (median 62 years). Elective neck dissection was performed in all patients (8 ipsilateral, 4 bilateral) and a total of 256 lymph nodes were remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…However, if a lymph node is examined only by one central section, micrometastases, which are typically localized in the subcapsular sinuses of lymph nodes, are likely to be missed [11]. For this reason, it is very difficult to diagnose micrometastases using routine histopathological examinations [10,12]. Many authors state significantly increased detection rate of micrometastases by examining serial histological sections in combination with immunohistochemical or molecular procedures [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, if a lymph node is examined only by one central section, micrometastases, which are typically localized in the subcapsular sinuses of lymph nodes, are likely to be missed [11]. For this reason, it is very difficult to diagnose micrometastases using routine histopathological examinations [10,12]. Many authors state significantly increased detection rate of micrometastases by examining serial histological sections in combination with immunohistochemical or molecular procedures [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies on micro-metastasis have been carried in gastric cancers, breast cancers, colorectal cancers, carcinomas of other sites and their results have shown that the detection of micro-metastasis has a significant difference in the recurrence and survival rate. 12,17 Čelakovský et al 18 recommended Elective neck dissection or radiotherapy of the neck should be considered in patients with high risk of occult metastases or micro-metastasis. 18 Thakare et al 5 in their study observed micro-metastatic carcinomatous cells in H and E staining of frozen section (FS) in 18 lymph nodes (54%) and in 19 lymph nodes (57%) in step-serial sectioned (SS) H and E-stained sections.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 Čelakovský et al 18 recommended Elective neck dissection or radiotherapy of the neck should be considered in patients with high risk of occult metastases or micro-metastasis. 18 Thakare et al 5 in their study observed micro-metastatic carcinomatous cells in H and E staining of frozen section (FS) in 18 lymph nodes (54%) and in 19 lymph nodes (57%) in step-serial sectioned (SS) H and E-stained sections. 5 Thome JA et al 19 results showed that intra-operative FS is a highly accurate and sensitive method to detect macro-metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although preoperative staging methods like ultrasound, CT and MRI have become more and more precise and effective, microscopic examination following ND still remains the gold standard for the detection of lymph node metastases. Nevertheless, if only micrometastases are present in the dissected lymph node, typically localized in the subcapsular sinuses of lymph nodes, pathologists can miss the tumor positivity [8,9,14]. Further studies should include this, e.g.…”
Section: Impact and Importance Of The Lnrmentioning
confidence: 99%